DISTRO ONLINE SHOP DENGAN FITUR CUSTOME MODE BERBASIS WEB MOBILE PADA DISTRO HORNY CUPCAKES - RISANG ADI PUTRAWAN, YOSSIE; Mariana, Novita (Information Technology and Telematics, 2018)
Abstract Horny Cupcakes Store is a shop that sells a variety of clothing products to support your daily appearance. The purpose of this study is to create a web-based clothing sales website mobile. The method used to build the system development is the waterfall method. System design using UML and system implementation using PHP and MySQL. The results of research on the Horny Cupcakes Store can be concluded that with the construction of mobile web sales clothing can help product marketing. And makes it easy for customers to make order transactions, and get information about Horny Cupcakes